Curative Mythmaking: Children's Bodies, Medical Knowledge, and the Frontier of Health in Early Soviet Odesa - Pauly, Matthew D. (East/West, 2022)
This essay explores how Soviet authorities appropriated medical knowledge derived from the treatment of a “passive” juvenile population to create a new assurance of municipal well-being in the 1920s. The attempt to control and remediate the spread of disease reflected a Bolshevik certainty in the state’s ability to confront the frontier of health by applying the dictates of modern science. Revolution and civil war brought challenge—the fractured city changed hands repeatedly until a final, tentative victory by the Red Army in 1920. Odesa’s children figuratively confronted a political, moral, and social liminality, standing between the diseased, corrupt yesteryear and a salubrious, principled future. Soviet central authorities sought to revive the newly liberated city by establishing a network of children’s institutions in which they would contain contagion, but also bring the full spectrum of applied expertise to bear on young bodies. In this traumatized city at the Soviet Union’s edge, state custodians would raise a new, loyal generation. Its health would signify revolution achieved. Illness would continue to plague the city’s residents, but the myth of a community united in health created an ecology of promise and activism.